PERAN GURU KELAS V SEBAGAI PEMBIMBING DALAM MENINGKATKAN MOTIVASI MOTIVASI BERPRESTASI DAN HUBUNGAN SOSIAL DI SD GMIT KUANFATU - Silvester Petrus Taneo; Treesly Y.N Adoe; Mirna Adriana Missa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted at GMIT Kuanfatu Elementary School with the research results showing that the role of the fifth grade teacher as a guide in increasing achievement motivation and social relations at GMIT Kuanfatu Elementary School consists of: (1) Listening and understanding students. The homeroom teacher provides opportunities for students to provide opinions or input (2) provide direction and encouragement. by guiding them to work together (3) helping students overcome obstacles. specially guided by teachers who have been assigned by the school so that students do not experience difficulties in increasing their learning motivation. (4) Learning skills. can help them to find out the learning skills their students have. (5) learning methods. using learning methods, for example the lecture method, question and answer and small group forms, so that it really helps students and also makes students enthusiastic about learning in class. (6) learning media. really motivates students and with the learning media students enjoy learning. (7) there are rewards or awards. providing numbers or values ​​as a form of motivation. (8) cooperate. familiarize students with communicating with the surrounding environment. According to the results of the research above, it can be concluded that the role of the fifth grade teacher as a guide in increasing achievement motivation and social relations at GMIT Kuanfatu Elementary School has been running effectively. The success or failure of the teacher's role as a guide all depends on the teacher.